2018
DOI: 10.1155/2018/9327403
|View full text |Cite
|
Sign up to set email alerts
|

Combined Effect of Vertical and Horizontal Ground Motions on Failure Probability of RC Chimneys

Abstract: Previous earthquake events have shown that chimneys are one of the most fragile structures. Studies have focused on the seismic behavior of reinforced concrete (RC) chimney structures subjected to earthquake load only along the horizontal direction. However, the vertical component of strong ground motion has been proven to damage or completely destroy civil structures. Therefore, it is essential to determine the failure probability of RC chimneys under both horizontal and vertical directions. In this study, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
(28 reference statements)
0
4
0
Order By: Relevance
“…e authors concluded that the increase in axial force will give rise to significant reduction in shear capacity and thus aggravate the possibility of shear failure. Guo et al [88] studied the combined effect of horizontal and vertical ground shaking on RC chimneys using fragility based assessment.…”
Section: Effects Of Vertical Shaking On Structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…e authors concluded that the increase in axial force will give rise to significant reduction in shear capacity and thus aggravate the possibility of shear failure. Guo et al [88] studied the combined effect of horizontal and vertical ground shaking on RC chimneys using fragility based assessment.…”
Section: Effects Of Vertical Shaking On Structuresmentioning
confidence: 99%
“…Although the scope of the paper is limited to building structures only, the authors recognize the notable contributions in the field of bridge engineering considering the effects of vertical excitation as reported elsewhere (see, e.g., [66,[96][97][98][99][100][101], among others). Despite buildings and bridges, many researchers have considered the vertical excitation to assess the seismic performance of various types of structures (e.g., [88,[102][103][104][105][106], among others).…”
Section: Effects Of Vertical Shaking On Structuresmentioning
confidence: 99%
“…A handful of studies is available on the seismic fragility of reinforced concrete (RC) chimneys via numerical models (e.g. Huang et al 2004;Gould and Huang 2006;Zhou et al 2015Zhou et al , 2019Guo et al 2018Guo et al , 2019Qiu et al 2020), while contributions on steel chimneys and process towers are very scarce (e.g. Lopez et al 1996;Moharrami and Amini 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Among these, Qu et al develop pushover methods for seismic assessment of buildings under multidimensional earthquakes, with the objective of overcoming the drawbacks of the conventional modal pushover method [17]. In other examples, Farahmand-Tabar and Barghian carry out a seismic assessment of a cable-stayed arch bridge under three-component orthotropic earthquake excitation [18], Lin et al investigate the seismic behavior of long-span connected structures under multisupported and multidimensional earthquake excitations [19], and Guo et al study the combined effect of vertical and horizontal ground motions on the failure probability of reinforced concrete chimneys [20]. Wang et al present a detailed review of the development and evaluation of multidimensional combination rules and their adoption in modern design codes and standards [21].…”
Section: Introductionmentioning
confidence: 99%